PEMIKIRAN SHI’AH ISMAILIYAH TENTANG KALENDER ISLAM Tinjauan atas Sistem Kalender Hisabi Dinasti Fatimiyah - Ahmad Musonnif (UIN Sayyid Ali Rahmatullah Tulungagung, 2016)
The Ismailites determine the beginning and the end of Ramadan based on hisab calendar and not on sighting the crescent. According to this Shi’it school, Ramadan always has 30 days. This argument is based on the normative propotitions, the Prophet’s traditions, the opinions of their imams and logical reasonings. As political policy, this calender was used as an instrument to legitimate the position of the Fatimid Imam, holder of religious authority and politics. Besides, the calender also functioned as an instrument of political identity which differ the school from the other Shi’ities school and Sunnite.Keywords: Calender, Hisab, Fatimid, Ismailiyah